Role of Vitamin D in Preventing and Treating Selected Extraskeletal Diseases-An Umbrella Review - Maretzke, Friederike; Bechthold, Angela; Egert, Sarah; Ernst, Jana B.; Melo van Lent, Debora; Pilz, Stefan; Reichrath, Jörg; Stangl, Gabriele I.; Stehle, Peter; Volkert, Dorothee; Wagner, Michael; Waizenegger, Julia; et al. (Nutrients, 2020)
Evidence is accumulating that vitamin D may have beneficial effects on respiratory tract, autoimmune, neuro-degenerative, and mental diseases. The present umbrella review of systematic reviews (SRs) of cohort studies and randomised controlled trials (RCTs), plus single Mendelian randomisation studies aims to update current knowledge on the potential role of vitamin D in preventing and treating these extraskeletal diseases. Altogether, 73 SRs were identified. Observational data on primary prevention suggest an inverse association between vitamin D status and the risk of acute respiratory tract infections (ARI), dementia and cognitive decline, and depression, whereas studies regarding asthma, multiple sclerosis (MS), and type 1 diabetes mellitus (T1DM) are scarce. SRs of RCTs support observational data only for the risk of ARI. No respective RCTs are available for the prevention of chronic obstructive pulmonary disease (COPD), MS, and T1DM. SRs of RCTs indicate beneficial therapeutic effects in vitamin D-deficient patients with asthma and COPD, while effects on major depression and T1DM need to be further elucidated. Mendelian randomisation studies do not consistently support the results of SRs. Since several limitations of the included SRs and existing RCTs do not permit definitive conclusions regarding vitamin D and the selected diseases, further high-quality RCTs are warranted.
CRIS-Team Scopus Importer:2020-04-17
Keywords: 25-hydroxyvitamin D (25(OH)D); asthma; ARI; COPD; dementia and cognitive decline; depression; multiple sclerosis; T1DM; umbrella review; vitamin D